The College of Medicine in the Republic of Malawi: towards sustainable staff development - Broadhead Robert L; Zijlstra Ed E (BMC, 2007)
Abstract Background Malawi has a critical human resources problem particularly in the health sector. There is a severe shortage of doctors; there are only few medical specialists. The College of Medicine (COM) is the only medical school and was founded in 1991. For senior staff it heavily depends on expatriates. In 2004 the COM started its own postgraduate training programme (Master of Medicine) in the clinical specialties. Methods We explore to what extent a brain drain took place among the COM graduates by investigating their professional development and geographical distribution. Using current experience with the postgraduate programme, we estimate at what point all senior academic positions in the clinical departments could be filled by Malawians. We demonstrate the need for expatriate staff for its most senior academic positions in the interim period and how this can be phased out. Lastly we reflect on measures that may influence the retention of Malawian doctors. Results Since the start of the COM 254 students have graduated with an average of 17 students per year. Most (60%) are working in Malawi. Of those working abroad, 60% are in various postgraduate training programmes. In 2015, adequate numbers of Malawi senior academics should be available to fill most senior positions in the clinical departments, taking into account a 65% increase in staff to cope with increasing numbers of students. Conclusion There seems to be no significant brain drain among graduates of the COM. The postgraduate programme is in place to train graduates to become senior academic staff. In the interim, the COM depends heavily upon expatriate input for its most senior academic positions. This will be necessary at least until 2015 when sufficient numbers of well trained and experienced Malawian specialists may be expected to be available. Improved pay structure and career development perspectives will be essential to consolidate the trend that most doctors will remain in the country.